Could saponins be used to enhance bioremediation of polycyclic aromatic hydrocarbons in aged-contaminated soils?. (March 2018) - Davin, Marie; Starren, Amandine; Deleu, Magali; Lognay, Georges; Colinet, Gilles; Fauconnier, Marie-Laure
Abstract: Polycyclic aromatic hydrocarbons (PAH) are persistent organic compounds of major concern that tend to accumulate in the environment, threatening ecosystems and health. Brownfields represent an important tank for PAHs and require remediation. Researches to develop bioremediation and phytoremediation techniques are being conducted as alternatives to environmentally aggressive, expensive and often disruptive soil remediation strategies. The objectives of the present study were to investigate the potential of saponins (natural surfactants) as extracting agents and as bioremediation enhancers on an aged-contaminated soil. Two experiments were conducted on a brownfield soil containing 15 PAHs. In a first experiment, soil samples were extracted with saponins solutions (0; 1; 2; 4 and 8 g.L −1 ). In a second experiment conducted in microcosms (28 °C), soil samples were incubated for 14 or 28 days in presence of saponins (0; 2.5 and 5 mg g −1 ). CO2 emissions were monitored throughout the experiment. After the incubation, dehydrogenase activity was measured as an indicator of microbiological activity and residual PAHs were determined. In both experiments PAHs were determined using High-Performance Liquid Chromatography and Fluorimetric Detection. The 4 g.L −1 saponins solution extracted significantly more acenaphtene, fluorene, phenanthrene, anthracene, and pyrene than water. PAHs remediation was not enhanced in presence of saponins compared to control samples after 28 days. However CO2 emissions and dehydrogenase activities were significantly more important in presence of saponins, suggesting no toxic effect of these surfactants towards soil microbiota. Highlights: Aged-soil washing by a 4 g.L −1 saponins solution extracted more PAHs than water. The addition of saponins to soil is not toxic towards the soil microbiota. PAHs bioremediation is not enhanced in presence of saponins after 28 days.